2003
DOI: 10.1074/jbc.m307397200
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Hydroxylase from Bacillus thermoglucosidasius A7, a Two-protein Component Monooxygenase with a Dual Role for FAD

Abstract: A novel phenol hydroxylase (PheA) that catalyzes the first step in the degradation of phenol in Bacillus thermoglucosidasius A7 is described. The two-protein system, encoded by the pheA1 and pheA2 genes, consists of an oxygenase (PheA1) and a flavin reductase (PheA2) and is optimally active at 55°C. PheA1 and PheA2 were separately expressed in recombinant Escherichia coli BL21(DE3) pLysS cells and purified to apparent homogeneity. The pheA1 gene codes for a protein of 504 amino acids with a predicted mass of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 81 publications
(80 reference statements)
4
106
0
Order By: Relevance
“…26) Recently, it was found that PheA2, which was the most similar to Bfl based on amino acid sequences, had flavin reductase activity. 40) The optimum temperature was 55 C and the remaining activity was 65% when PheA2 was incubated at 65 C for 2 h. Bfl had optimal activity at 70 C and retained 90% of the activity even after the enzyme was treated at 70 C for 30 min (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26) Recently, it was found that PheA2, which was the most similar to Bfl based on amino acid sequences, had flavin reductase activity. 40) The optimum temperature was 55 C and the remaining activity was 65% when PheA2 was incubated at 65 C for 2 h. Bfl had optimal activity at 70 C and retained 90% of the activity even after the enzyme was treated at 70 C for 30 min (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is necessary to investigate further to make clear the functions of ORF2, 3, and 4, it is thought that Bfl is not an enzyme that couples with a specific monooxygenase. In 1999, it was shown that ferric reductase (FeR) from a hyperthermophilic archeon, Archaeoglobus fulgidus, shared amino acid similarity with a family of flavin reductase, 33) and the three-dimensional structures of FeR and PheA2 were elucidated and compared 40,43) Nevertheless, it was reported that FeR had flavin reductase activity and that PheA2 had no ferric reductase activity. 40) In this study we confirmed that Bfl had ferric reductase activity.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…1). The amino acid sequence of Phe shares a 31% identity with phenol hydroxylase from Trichosporon cutaneum (Enroth et al, 1998), and shares 19%, 15% and 15% identities with phenol hydroxylase from Pseudomonas pickettii PKO1 (Kukor and Olsen, 1990), Bacillus thermoglucosidasius A7 (Kirchner et al, 2003) and Bacillus stearothermophilus BR219 (Kim and Oriel, 1995), respectively (Table 2). Interestingly, the putative phenol hydroxylase in C. glutamicum did not show a significant similarity with either multi-component or twocomponent phenol hydroxylases that are widely distributed in bacteria.…”
Section: Sequence Analysis Of a Putative Phenol Hydroxylase In C Glumentioning
confidence: 99%
“…This NADH:FMN oxidoreductase or flavin reductase family was first described in the early 1990s and exists in many organisms, primarily Gram-negative bacteria (Uetz et al, 1992;Blanc et al, 1995). These short-chain flavin reductases are involved in a variety of biological reactions and often act in concert with a flavin-dependent monooxygenase which oxidizes through the addition of molecular oxygen (Kirchner et al, 2003;Galá n et al, 2000). However, they do not share sequence homology with flavin reductases found in E. coli or luminous bacteria or with the LuxG protein class found in lux operons (Nijvipakul et al, 2008).…”
Section: Comparison With Other Short-chain Flavin Reductasesmentioning
confidence: 99%